Equality of Opportunity for Sexual and Gender Minorities - Cortez, Clifton; Arzinos, John; De la Medina Soto, Christian (Washington, DC: World Bank, 2021)
Despite legal and social advances in the past two decades, sexual orientation and gender minorities continue to face widespread discrimination and violence in many countries. This discrimination and violence lead to exclusion, which adversely impacts their lives, as well as the communities and economies in which they live.